Seedling Journal for Family Research in the Orinoquía: a bridge between academia, the community and public policies (Boletín Semillero de Investigación en Familia, 2024)
The Research Seedbed Journal on Family in the Orinoquía has established itself as a fundamental platform for disseminating academic knowledge about families in the region, promoting a comprehensive approach based on the social determinants of health. Since its inception, it has addressed various issues related to family, family health, education, public policy, and sustainable development, highlighting its impact on the formulation of community strategies and territorial policies. Its work goes beyond academia by connecting researchers, communities, and decision-makers, contributing to the construction of a more equitable and sustainable Orinoquía.